2014
DOI: 10.1111/mec.12830
|View full text |Cite
|
Sign up to set email alerts
|

Climatic adaptation and ecological divergence between two closely related pine species in Southeast China

Abstract: Climate is one of the most important drivers for adaptive evolution in forest trees. Climatic selection contributes greatly to local adaptation and intraspecific differentiation, but this kind of selection could also have promoted interspecific divergence through ecological speciation. To test this hypothesis, we examined intra- and interspecific genetic variation at 25 climate-related candidate genes and 12 reference loci in two closely related pine species, Pinus massoniana Lamb. and Pinus hwangshanensis His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 136 publications
4
43
0
Order By: Relevance
“…Mountain uplift and past environmental oscillations may have been largely responsible for shaping the spatial patterns of diversity and genetic divergence among species (Coyne and Orr, 2004; Wachowiak et al, 2009). In general, the level and distribution of nucleotide diversity are historical products of the long-term evolution of a species, and they are largely associated with the evolutionary potential or future fate of a species (Wright and Gaut, 2005; Wachowiak et al, 2009; Zhou et al, 2014; Tsuda et al, 2017). In addition, ecological or proximal causes (e.g., mating systems) and various barriers (e.g., geographic and spatio-temporal isolation) due to geological history can cause fragmented of species distributions, which may lead to reduced gene flow between isolated populations and adaptability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mountain uplift and past environmental oscillations may have been largely responsible for shaping the spatial patterns of diversity and genetic divergence among species (Coyne and Orr, 2004; Wachowiak et al, 2009). In general, the level and distribution of nucleotide diversity are historical products of the long-term evolution of a species, and they are largely associated with the evolutionary potential or future fate of a species (Wright and Gaut, 2005; Wachowiak et al, 2009; Zhou et al, 2014; Tsuda et al, 2017). In addition, ecological or proximal causes (e.g., mating systems) and various barriers (e.g., geographic and spatio-temporal isolation) due to geological history can cause fragmented of species distributions, which may lead to reduced gene flow between isolated populations and adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…They are mainly characterized by long life cycles, large effective population sizes, incomplete lineage sorting, and extensive introgression/hybridization among populations, which makes their genetic structure and spatial patterns of diversity very different from those found in traditional model plants (Neale and Kremer, 2011; Gao et al, 2012; Li et al, 2012, 2013; Hao et al, 2015). For instance, conifers tend to share haplotypes/genotypes among species, with no distinct genetic divergence across species ranges, and most of the genetic variations are found within populations (Willyard et al, 2009; Chen et al, 2010; Ren et al, 2012; Liu et al, 2014; Zhou et al, 2014). In recent years, many studies have determined nucleotide polymorphisms and speciation history patterns using multiple nuclear loci (Ma et al, 2006; Li et al, 2010; Gao et al, 2012; Wachowiak et al, 2013; Zhou et al, 2014; Zou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yongfeng Zhou et al used two closely related pine species growing in southeastern Chinese, Pinus massoniana Lamb and Pinus hwangshanensis Hisa as materials, to analyse 25 climate related genes.They found that variations in climate played an important role in the ecological divergence of the two species [2]. Not only on the woody perennial plants, climate also has a similar impact on the annual herbaceous plants such as Arabidopsis, barley and so on [3].…”
Section: Introductionmentioning
confidence: 99%